Reflections about the right to choose freely among products and services: a brief case study1 - Fuentes Veliz, Juan Andrés (2016)
In Peru, the right to choose freely among products and services has not been developed in extent, right contained in the Code of Protection and Defense of the Consumer. In that order of ideas, this right is not alleged in courts to be enforced due its content is not well known. Therefore, our research has the purpose of analyzing common situations, where the right to choose freely among products and services is discussed with the objective to limiting its scope clear and evenly, which would greatly contribute to its compliance.